A Comparative Assessment of Designs of Hairline Patterns in Patients Undergoing Hair Transplant - Kamal Uddin Khan, Farzana Abdullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hair loss affects millions of people globally by generating psychological distress together with a diminished sense of self-confidence. Modern hair transplant surgery presents patients with an established means to achieve natural hairline recovery. Improper hairline design results in aesthetically displeasing pluggy appearance which leads to psychological distress among patients. Materials and Methods: A comparative cross-sectional study was conducted from January 2022 to September 2022. In this study, a total of 100 patients was recruited by using random non-convenient sampling method after obtaining prior written informed consent from all the study participants. In this study, all the patients undergoing hair transplant due to androgenic alopecia, age-related alopecia and alopecia due to scarring were included. Results: A total of 50 patients were recruited for the study with the mean age of 33.82 + 4.99 years of age. Post transplantation, degree of hair fall and hairline pattern was also assessed using Norwood Hamilton scale and it was observed that hairline pattern improved significantly as explained in table 3 and up till grade 4 it was noticed that all the patients reverted back to the type 1. Conclusion: The research delivers significant information about hairline styles as well as transplantation performance assessment at a tertiary care center located in Balochistan Pakistan. Most patients benefited from their hair transplant procedures by showing substantial development in their hairline patterns according to lower Norwood-Hamilton grade assessments after treatment. Keywords: hair transplant, alopecia, androgenic, hairline patterns,